2000
DOI: 10.1111/1468-0262.00150
|View full text |Cite
|
Sign up to set email alerts
|

Capital-skill Complementarity and Inequality: A Macroeconomic Analysis

Abstract: The supply and price of skilled labor relative to unskilled labor have changed dramatically over the postwar period. The relative quantity of skilled labor has increased substantially, and the skill premium, which is the wage of skilled labor relative to that of unskilled labor, has grown significantly since 1980. Many studies have found that accounting for the increase in the skill premium on the basis of observable variables is difficult and have concluded implicitly that latent skill-biased technological ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
811
5
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,386 publications
(942 citation statements)
references
References 23 publications
45
811
5
4
Order By: Relevance
“…In Section 3, we introduce the nested constant elasticity of substitution production function (Sato (1967) and Krusell et. al.…”
Section: Figure 1 About Herementioning
confidence: 99%
“…In Section 3, we introduce the nested constant elasticity of substitution production function (Sato (1967) and Krusell et. al.…”
Section: Figure 1 About Herementioning
confidence: 99%
“…We also include the special case examined by Krusell et al (2000) and demonstrate how technical progress terms may be identified in this case. Then section 3.3 makes the equivalent analysis for the four-factor, two-level CES case.…”
Section: Multi-level Multi-factor Ces Production Functionsmentioning
confidence: 99%
“…the direction can only be exogenous or endogenous. 3 The first case -the technology push story -is a general label under more specific mechanisms are put forth, such the technological revolution (Caselli, 1999), the decline in the price of ICT capital (Autor et al 2003, Krusell et al 2000, the introduction of General Purpose Technology (Aghion, 2002). The second case is the one in which technological change is directed because of profits incentives.…”
Section: From the Canonical Model To The Ricardian Modelmentioning
confidence: 99%